The Fresh Start Mindset: Transforming Consumers’ Lives - Price, Linda L; Coulter, Robin A; Strizhakova, Yuliya; Schultz, Ainslie E (Journal of Consumer Research, 2018)
AbstractThis article introduces the fresh start mindset, defined as a belief that people can make a new start, get a new beginning, and chart a new course in life, regardless of their past or present circumstances. With historical roots in American culture and neoliberalism, and with contemporary links to liquid modernity and global consumer culture, this mindset structures reasoning, experience, and everyday language, and guides behavior across self- and other-transformative consumption domains. We develop a six-item scale (FSM) to measure the fresh start mindset and situate it within a broader nomological network, including growth mindset, personal capacity for change, optimism, future temporal focus, internal locus of control, self-efficacy, perseverance, resilience, and consumer variety seeking. Individuals with a stronger (vs. weaker) fresh start mindset invest in transformative change through changing their circumstances, including their own consumption choices (e.g., buying a new pair of sunglasses and getting a new self); they also are more supportive of transformative programs that assist those who are challenged to get a fresh start (i.e., disadvantaged youth, at-risk teens, veterans, and tax-burdened adults). Our work significantly contributes to transformative consumer research with attention to self-activities and programs for vulnerable populations that enable new beginnings.